Obedience, Self‐Control, and the Voice of Culture. (September 2014) - Ent, Michael R.; Baumeister, Roy F.; Haslam, S. Alexander; Miller, Arthur G.; Reicher, Stephen D.
<x xml:space="preserve">Abstract</x> Milgram's obedience studies dramatically demonstrated how obeying authority can have grim consequences. Nevertheless, we propose that obedience to legitimate authority is a vital aspect of human culture. Among other things, obedience to authority can encourage individuals to set aside their selfish desires for the good of their group. Often, such selfish desires are violent in nature. Thus, obedience can function to limit violence. We challenge the notion that people typically respond to the commands of authority with blind obedience. Last, we suggest that the implications of Milgram's findings have in some cases been overstated.